Self-Efficacy and Decision-Making among Educated Women: A Comprehensive Review of Theoretical and Empirical Studies (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Women's empowerment has emerged as a central theme in contemporary social, educational, and developmental research. Among the various dimensions of empowerment, self-efficacy and decision-making power occupy a prominent position because they directly influence women's ability to exercise autonomy, pursue opportunities, and participate effectively in personal, professional, and social domains. Higher education has been recognized as a major factor contributing to the development of self-efficacy and decision-making capabilities among women. This review paper examines the theoretical foundations and empirical evidence concerning the relationship between self-efficacy and decision-making among educated women. Drawing upon Bandura's Social Cognitive Theory and women's empowerment frameworks, the study synthesizes findings from national and international literature. The review demonstrates that educational attainment significantly enhances women's confidence, competence, and perceived control over life events, which in turn strengthens decision-making authority. The paper also identifies key determinants, challenges, and research gaps while suggesting directions for future research. The findings indicate that self-efficacy functions as an important psychological mechanism through which education contributes to women's empowerment and autonomy.